Evaluation of Overall Performance of Faculty Members by Using Self-Assessment Method - Shah, Santosh; Kumar, Anand; Pokharel, Nabaraj (Journal of Universal College of Medical Sciences, 2020)
INTRODUCTION The quality of teaching–learning process at medical college depends mainly of infrastructure that includes competent personnel, optimal teaching space and equipment in accordance with existing standards and norms.Faculty hence remains the cornerstone of overall academic performance of institution. Faculty evaluation and faculty development training strengthens further academic excellence. Self-assessment of their own teaching performance by faculties is highly efficient for further academic improvement and enhancement. MATERIAL AND METHODS A Cross sectional, prospective study was conducted among 134 faculty members of various departments at Universal Medical College and Teaching Hospital (UCMS), Bhairahawa in month of June 2019. Faculty from clinical, basic, dental and nursing sciences were included in this study. Assessment were done with standard questionnaire with 8 different variables was using the Likert scale. A semi-structured self-administered questionnaire was used for collection of data. All the respondents provided opinion regarding level of skill, level of dependability, skill in patient relation, commitment to organization, efficiency to organize work, overall quality deliver to workplace, productivity, level of team work by a 5 points rating scale. They were provided with questionnaire and they are asked to fill form with using self-assessment methods. Data were analyzed using Microsoft excel and represented as frequency and proportion. RESULTS A total of 134 lecturers from various faculties participated in this study. Majority of participants (40%) are from basic sciences. In this study majority of faculties assessed themselves as competent in regards of skill (12%), clinical faculties find themselves efficient in regard of organization of work schedule. Sixteen participants found themselves dependent on others in their work. When they were asked to rate their patient related skills, six members from basic sciences were unsatisfied while all the clinicians find that they meet the job requirement and expectations. All participants believe in team work and majority of them were committed towards the organization. CONCLUSION The self-assessment by faculty themselves is equally effective to plan faculty development programs for further improvement and enhancement.